(untitled) (Scientific journal of the Fergana State University, 2024)
Pedagogical skill and competence is the result of each teacher’s self work and creative work. The development of pedagogical competence is organized based on the use of various forms and methods, special didactic principles, relying on pedagogical and psychological laws. The article holds exactly that view.